In vitro activity of isavuconazole against fluconazole-resistant isolates of Histoplasma capsulatum - Spec, Andrej (Med Mycol, 2018)
No clinical trials for histoplasmosis have been performed with the newer azoles, leaving itraconazole as the azole of choice. In vitro studies suggest that Histoplasma capsulatum from patients that relapse on fluconazole has higher minimum inhibitory concentrations (MICs) to fluconazole and voriconazole but not itraconazole and posaconazole. The newest azole, isavuconazole, shares structural similarity to voriconazole, but to date nobody has explored emergence of resistance. In vitro susceptibilities to isavucoanzole and fluconazole were performed on previously obtained isolates from the patients who relapsed on fluconazole therapy. Susceptibilities were determined by NCCLS method M27A developed for yeasts, as modified for H. capsulatum. The change in the MIC from the primary to the relapse isolate was tested using Wilcoxon Rank-Sum for paired data. Among the primary isolates, the median MICs were 1.0 (range 0.25 to 4.0) μg/ml for fluconazole and ≤0.007 (range ≤0.007 to 0.015) μg/ml for isavuconazole. In the group of relapsed isolates, the median MICs rose to 8.0 (range 0.25 to 64.0) μg/ml for fluconazole and remained unchanged at ≤0.007 (range ≤0.007 to 0.015) μg/ml for isavuconazole (P < .001). Only one isolate exhibited a nonsignificant increase in MIC to isavuconazole. Histoplasma isolates from patients who relapsed on fluconazole did not have an elevation in MICs to isavuconazole. This differs from the results previously seen with voriconazole and suggests that despite a closer structural similarity to voriconazole than itraconazole and posaconazole, isavuconazole has a higher barrier to resistance and may be effective as therapy for histoplasmosis.